Everolimus treatment for neuroendocrine tumors: latest results and clinical potential. (March 2017) - Pusceddu, Sara; Verzoni, Elena; Prinzi, Natialie; Mennitto, Alessia; Femia, Daniela; Grassi, Paolo; Concas, Laura; Vernieri, Claudio; Lo Russo, Giuseppe; Procopio, Giuseppe
Neuroendocrine tumors (NETs) are a heterogeneous class of diseases characterized by challenging management. Preclinical evidence shows that the PI3K/AKT/mTOR signaling pathway plays a central role in the pathogenesis and progression of NETs. Everolimus is a direct inhibitor of this pathway, and therefore this molecule appears to be a well-grounded strategy for the treatment of NETs, capable of changing clinical practice. The efficacy and safety of everolimus was demonstrated in the RADIANT trials. In this work, we comment on the results of the RADIANT trials, and other recent key evidence from fully published clinical trials on everolimus, and we discuss the current role of everolimus in the treatment of NETs.